2017
DOI: 10.1002/jmri.25589
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the rabbit supraspinatus enthesis at 7 Tesla: a 4‐week time course after repair surgery and effect of channeling

Abstract: 2 Technical Efficacy: Stage 1 J. MAGN. RESON. IMAGING 2017;46:461-467.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…For this study, we accessed a tissue bank containing shoulders from female New Zealand white rabbits (3.0 ± 0.3 kg) that had been used for magnetic resonance imaging analysis (Trudel et al, 2017) and mechanical testing after RC anchor repair (Louati et al, 2018). From the tissue bank, we retrieved all samples (n = 42) that were suitable for histological analysis.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, we accessed a tissue bank containing shoulders from female New Zealand white rabbits (3.0 ± 0.3 kg) that had been used for magnetic resonance imaging analysis (Trudel et al, 2017) and mechanical testing after RC anchor repair (Louati et al, 2018). From the tissue bank, we retrieved all samples (n = 42) that were suitable for histological analysis.…”
Section: Animalsmentioning
confidence: 99%
“…All rabbits were euthanized with a pentobarbital overdose at the prespecified postoperative times. Shoulders were harvested en bloc, individually wrapped in saline-soaked gauze to avoid dehydration, and immediately frozen at −20°C (Trudel et al, 2017). Thawed shoulder samples were mechanically tested to failure using an electromechanical load-frame.…”
Section: Collection Of Specimens and Biomechanical Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fukawa et al 53 reported that changes in the T2 value of magnetic resonance image T2 mapping reflected histologic tendon healing. Trudel et al 54 showed that reformation of the supraspinatus tendon after repair was characterized by increasing T2 values. Krepkin et al 55 demonstrated that there was a negative correlation between T2 values and SWE values in the supraspinatus tendon, and these results for the repaired tendon were consistent with our results.…”
Section: Stiffness Change After Arcrmentioning
confidence: 99%
“…Twenty-fold increase in cellularity was measured 1-2 weeks after channeling in the animal model (26). However, channeling did not improve enthesis reformation after SSP repair in the rabbit model (27). The effect of channeling on the SSP tendon proper remains unknown.…”
Section: Introductionmentioning
confidence: 99%